Photocatalyst water-based paint and preparation method thereof

Through Ce modification and coating technology, modified TiO2 has photocatalytic activity under visible light, solving the problem that TiO2 is only effective under ultraviolet light, and achieving a wider application in daily life scenarios.

CN119432147AActive Publication Date: 2025-02-14JIANGMEN SANSHANG NEW MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411562573.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

As a photocatalyst material, TiO2 has good photocatalytic activity only under ultraviolet light and cannot be utilized for about 96% of visible light, limiting its use in daily life scenarios.

Method used

TiO2 is modified by Ce and coated with N-(3-dimethylaminopropyl)methacrylamide. The modified TiO2 can exert a photocatalytic effect under visible light.

Benefits of technology

Modified TiO2 significantly improves the visible light absorption performance of TiO2, ensures that it has photocatalytic activity under visible light, and disperses it evenly in the coating through coating, improving the coating performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118282600000021
    Figure BDA0005118282600000021
  • Figure BDA0005118282600000031
    Figure BDA0005118282600000031
  • Figure BDA0005118282600000101
    Figure BDA0005118282600000101
Patent Text Reader

Abstract

The invention relates to a photocatalyst water-based paint and a preparation method thereof, and belongs to the technical field of paints. In the modified TiO2 of the photocatalyst water-based paint, Ce is used for modifying TiO2, so that the visible light absorption performance of TiO2 is remarkably improved. And secondly, Ce-modified TiO2 is coated with N-(3-dimethylaminopropyl) methacrylamide, so that the Van der Waals gravitational action between TiO2 can be remarkably reduced, and the Ce-modified TiO2 is uniformly dispersed in the coating. Moreover, after the surface of the Ce-modified TiO2 is coated with N-(3-dimethylaminopropyl) methacrylamide, poly N-(3-dimethylaminopropyl) methacrylamide is formed, and the problem that the Ce-modified TiO2 is difficult to directly contact with formaldehyde due to coating is relieved. And finally, N element is introduced into TiO2 by N-(3-dimethylaminopropyl) methacrylamide, so that the visible light absorption range of TiO2 is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coatings, and in particular, relates to a photocatalyst water-based coating and a preparation method thereof. Background Art

[0002] TiO2 is an important photocatalyst material that can catalytically degrade organic pollutants such as formaldehyde and toluene under ultraviolet light, and it also has the advantages of being antibacterial, non-toxic, and acid- and alkali-resistant. However, as a photocatalyst, TiO2 only has good photocatalytic activity under ultraviolet light and cannot utilize approximately 96% of visible light, which severely limits the use of TiO2 as an important photocatalyst material in daily life scenarios. Summary of the invention

[0003] The first object of the present invention is to provide a photocatalyst water-based paint that can exert a photocatalytic effect under visible light.

[0004] The second object of the present invention is to provide a method for preparing the above-mentioned water-based coating.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A photocatalyst water-based paint comprises photocatalyst material-modified TiO2, wherein the modified TiO2 is prepared by the following operations:

[0007] Preparation of Ce-modified TiO2: evenly mix anhydrous ethanol and cerium nitrate aqueous solution to obtain a mixed solution; mix the mixed solution with titanium tetrachloride, heat to react, and cool after the reaction to obtain Ce-modified TiO2;

[0008] Pretreatment: crush Ce-modified TiO2 into powder and then disperse it in ethanol by ultrasonic to obtain a 5-10wt% TiO2 suspension; dissolve N-(3-dimethylaminopropyl)methacrylamide in ethanol to obtain a 8-12wt% mixed solution;

[0009] Coating reaction: Mix the TiO2 suspension prepared in the pretreatment with the mixed solution, then add the catalyst ammonium persulfate or azobisisobutyronitrile and the surfactant sodium dodecyl sulfate, mix well, heat to react, and irradiate with ultraviolet light after the reaction is completed;

[0010] Post-treatment: After the ultraviolet lamp irradiation is completed, the product is centrifuged and dried to obtain modified TiO2.

[0011] As a preferred embodiment of the present invention, in the preparation of Ce-modified TiO2, the concentration of the cerium nitrate aqueous solution is 0.5-1.5 mol / L.

[0012] As a preferred embodiment of the present invention, in the preparation of Ce-modified TiO2, the temperature of the heating reaction is 130-180°C, and the time of the heating reaction is 6-10 hours.

[0013] As a preferred embodiment of the present invention, in the preparation of Ce-modified TiO2, the molar ratio of cerium nitrate to titanium tetrachloride is 1-5%.

[0014] As a preferred embodiment of the present invention, in the coating reaction, the mass ratio of TiO2 to N-(3-dimethylaminopropyl)methacrylamide is controlled to be 1:50-60.

[0015] As a preferred embodiment of the present invention, in the coating reaction, the temperature-raising reaction is specifically carried out at 60 to 80° C. for 1.5 to 3.5 hours.

[0016] As a preferred embodiment of the present invention, in the coating reaction, the irradiation with ultraviolet light is specifically performed with a light intensity of 2 to 4 mW / cm 2 Irradiate with ultraviolet light for 20 to 30 minutes.

[0017] As a preferred embodiment of the present invention, in the coating reaction, the mass of the catalyst is 0.1-1% of the mass of TiO2, and the mass of the surfactant is 0.5-1% of the mass of TiO2.

[0018] As a preferred embodiment of the present invention, the following components in parts by weight are included:

[0019]

[0020]

[0021] The preparation method of the above-mentioned photocatalyst water-based paint includes the following operations: quantitatively weighing water, cellulose, dispersant, and wetting agent and stirring evenly, then adding modified TiO2 and pigment for dispersion and grinding, adding BASF pure acrylic emulsion, and then adding defoamer and thickener after dispersion evenly, mixing evenly, and preparing photocatalyst water-based paint.

[0022] Beneficial effects of the present invention:

[0023] In the modified TiO2 of the photocatalyst water-based paint of the present invention, Ce is used to modify TiO2, Ce does not change the crystal form of TiO2, and significantly improves the visible light absorption performance of TiO2.

[0024] Secondly, Ce-modified TiO2 is coated with N-(3-dimethylaminopropyl)methacrylamide. TiO2 has a large specific surface area and Gibbs free energy, and its thermodynamic state is unstable. When TiO2 is directly added to the coating, the particles are close to each other due to the van der Waals attraction, and TiO2 changes from a dispersed state to an agglomerated state, thereby affecting the final coating performance of the coating. The coating can significantly reduce the van der Waals attraction between TiO2, making it evenly dispersed in the coating. In addition, after N-(3-dimethylaminopropyl)methacrylamide is coated on the surface of Ce-modified TiO2, poly-N-(3-dimethylaminopropyl)methacrylamide is formed, carboxyl groups and tertiary amine groups are introduced, and in the presence of Ce, it can partially react with formaldehyde to absorb formaldehyde. At the same time, after the reaction, the coated Ce-modified TiO2 is more exposed, alleviating the problem that Ce-modified TiO2 is difficult to directly contact with formaldehyde due to the coating. Finally, N-(3-dimethylaminopropyl)methacrylamide introduces the N element into TiO2, and part of the N element enters TiO2, reducing the band gap of TiO2, thereby broadening the visible light absorption range of TiO2. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with specific implementation methods.

[0026] Example 1

[0027] A modified TiO2 is prepared by the following operations:

[0028] Preparation of Ce-modified TiO2: Place 3.35 L of anhydrous ethanol in a container, add 0.5 mol / L of cerium nitrate aqueous solution and mix evenly to obtain a mixed solution; add 2.65 L of titanium tetrachloride to the mixed solution while stirring until a sol-state substance is formed, react it at 130 °C for 6 h, and naturally cool it after the reaction to obtain a solid. Wash the solid three times with anhydrous ethanol, filter and dry to obtain Ce-modified TiO2, wherein the molar ratio of cerium nitrate to titanium tetrachloride is 1%.

[0029] Pretreatment: Ce-modified TiO2 was ultrasonically dispersed in ethanol for 30 minutes to obtain a 5wt% TiO2 suspension; N-(3-dimethylaminopropyl)methacrylamide was dissolved in ethanol to obtain an 8wt% mixed solution.

[0030] Coating reaction: The TiO2 suspension and mixed solution prepared in the pretreatment were slowly added into the glass reactor, wherein the mass ratio of TiO2 to N-(3-dimethylaminopropyl)methacrylamide was 1:50; then the catalyst ammonium persulfate and the surfactant sodium dodecyl sulfate were added, stirred evenly, and reacted at 60°C for 1.5h. After the reaction was completed, the light intensity was 2mW / cm 2The catalyst mass is 0.1% of the mass of TiO2, and the surfactant mass is 0.5% of the mass of TiO2.

[0031] Post-treatment: After the reaction is completed, the product is centrifuged and washed with ethanol three times. The washed product is dried in an oven to constant weight to obtain modified TiO2.

[0032] Example 2

[0033] A modified TiO2 is prepared by the following operations:

[0034] Preparation of Ce-modified TiO2: Place 3.35 L of anhydrous ethanol in a container, add 0.8 mol / L of cerium nitrate aqueous solution and mix evenly to obtain a mixed solution; add 2.65 L of titanium tetrachloride to the mixed solution while stirring until a sol-state substance is formed, react it at 140°C for 7 hours, and naturally cool it after the reaction to obtain a solid. Wash the solid three times with anhydrous ethanol, filter and dry to obtain Ce-modified TiO2, wherein the molar ratio of cerium nitrate to titanium tetrachloride is 2%.

[0035] Pretreatment: Ce-modified TiO2 was ultrasonically dispersed in ethanol for 30 minutes to obtain a 6wt% TiO2 suspension; N-(3-dimethylaminopropyl)methacrylamide was dissolved in ethanol to obtain a 9wt% mixed solution.

[0036] Coating reaction: The TiO2 suspension and mixed solution prepared in the pretreatment were slowly added into the glass reactor, wherein the mass ratio of TiO2 to N-(3-dimethylaminopropyl)methacrylamide was 1:52; then the catalyst ammonium persulfate and the surfactant sodium dodecyl sulfate were added, stirred evenly, and reacted at 65°C for 2h. After the reaction was completed, the light intensity was 2.5mW / cm 2 The catalyst mass is 0.8% of the mass of TiO2, and the surfactant mass is 0.6% of the mass of TiO2.

[0037] Post-treatment: After the reaction is completed, the product is centrifuged and washed with ethanol three times. The washed product is dried in an oven to constant weight to obtain modified TiO2.

[0038] Example 3

[0039] A modified TiO2 is prepared by the following operations:

[0040] Preparation of Ce-modified TiO2: Place 3.35 L of anhydrous ethanol in a container, add 1.0 mol / L of cerium nitrate aqueous solution and mix evenly to obtain a mixed solution; add 2.65 L of titanium tetrachloride to the mixed solution while stirring until a sol-state substance is formed, react it at 150 °C for 8 h, and naturally cool it after the reaction to obtain a solid. Wash the solid three times with anhydrous ethanol, filter and dry to obtain Ce-modified TiO2, wherein the molar ratio of cerium nitrate to titanium tetrachloride is 3%.

[0041] Pretreatment: Ce-modified TiO2 was ultrasonically dispersed in ethanol for 30 minutes to obtain an 8wt% TiO2 suspension; N-(3-dimethylaminopropyl)methacrylamide was dissolved in ethanol to obtain a 10wt% mixed solution.

[0042] Coating reaction: The TiO2 suspension and mixed solution prepared in the pretreatment were slowly added into the glass reactor, wherein the mass ratio of TiO2 to N-(3-dimethylaminopropyl)methacrylamide was 1:55; then the catalyst ammonium persulfate and the surfactant sodium dodecyl sulfate were added, stirred evenly, and reacted at 70°C for 2.5h. After the reaction was completed, the light intensity was 3mW / cm 2 The catalyst mass is 0.3% of the mass of TiO2, and the surfactant mass is 0.8% of the mass of TiO2.

[0043] Post-treatment: After the reaction is completed, the product is centrifuged and washed with ethanol three times. The washed product is dried in an oven to constant weight to obtain modified TiO2.

[0044] Example 4

[0045] A modified TiO2 is prepared by the following operations:

[0046] Preparation of Ce-modified TiO2: Place 3.35 L of anhydrous ethanol in a container, add 1.2 mol / L of cerium nitrate aqueous solution and mix evenly to obtain a mixed solution; add 2.65 L of titanium tetrachloride to the mixed solution while stirring until a sol-state substance is formed, react it at 160°C for 9 hours, and naturally cool it after the reaction to obtain a solid. Wash the solid three times with anhydrous ethanol, filter and dry to obtain Ce-modified TiO2, wherein the molar ratio of cerium nitrate to titanium tetrachloride is 4%.

[0047] Pretreatment: Ce-modified TiO2 was ultrasonically dispersed in ethanol for 30 minutes to obtain a 9wt% TiO2 suspension; N-(3-dimethylaminopropyl)methacrylamide was dissolved in ethanol to obtain an 11wt% mixed solution.

[0048] Coating reaction: The TiO2 suspension and mixed solution prepared in the pretreatment were slowly added into the glass reactor, wherein the mass ratio of TiO2 to N-(3-dimethylaminopropyl)methacrylamide was 1:58; then the catalyst azobisisobutyronitrile and the surfactant sodium dodecyl sulfate were added, stirred evenly, and reacted at 75°C for 3h. After the reaction was completed, the light intensity was 3.5mW / cm 2 The catalyst mass is 0.5 of the mass of TiO2, and the surfactant mass is 0.9% of the mass of TiO2.

[0049] Post-treatment: After the reaction is completed, the product is centrifuged and washed with ethanol three times. The washed product is dried in an oven to constant weight to obtain modified TiO2.

[0050] Example 5

[0051] A modified TiO2 is prepared by the following operations:

[0052] Preparation of Ce-modified TiO2: Place 3.35 L of anhydrous ethanol in a container, add 1.5 mol / L of cerium nitrate aqueous solution and mix evenly to obtain a mixed solution; add 2.65 L of titanium tetrachloride to the mixed solution while stirring until a sol-state substance is formed, react it at 180°C for 10 hours, and naturally cool it after the reaction to obtain a solid. Wash the solid three times with anhydrous ethanol, filter and dry to obtain Ce-modified TiO2, wherein the molar ratio of cerium nitrate to titanium tetrachloride is 5%.

[0053] Pretreatment: Ce-modified TiO2 was ultrasonically dispersed in ethanol for 30 minutes to obtain a 10wt% TiO2 suspension; N-(3-dimethylaminopropyl)methacrylamide was dissolved in ethanol to obtain a 12wt% mixed solution.

[0054] Coating reaction: The TiO2 suspension and mixed solution prepared in the pretreatment were slowly added into the glass reactor, wherein the mass ratio of TiO2 to N-(3-dimethylaminopropyl) methacrylamide was 1:60; then the catalyst azobisisobutyronitrile and the surfactant sodium dodecyl sulfate were added, stirred evenly, and reacted at 80°C for 3.5h. After the reaction was completed, the light intensity was 4mW / cm 2 The catalyst mass is 1% of the mass of TiO2, and the surfactant mass is 1% of the mass of TiO2.

[0055] Post-treatment: After the reaction is completed, the product is centrifuged and washed with ethanol three times. The washed product is dried in an oven to constant weight to obtain modified TiO2.

[0056] Comparative Example 1

[0057] A modified TiO2, compared with Example 3, does not use Ce to modify TiO2, and the rest is the same as Example 3, and is prepared by the following operations:

[0058] Pretreatment: Ultrasonic dispersion of TiO2 in ethanol for 30 minutes to obtain an 8wt% TiO2 suspension; dissolve N-(3-dimethylaminopropyl)methacrylamide in ethanol to obtain a 10wt% mixed solution.

[0059] Coating reaction: The TiO2 suspension and mixed solution prepared in the pretreatment were slowly added into the glass reactor, wherein the mass ratio of TiO2 to N-(3-dimethylaminopropyl)methacrylamide was 1:55; then the catalyst ammonium persulfate / azobisisobutyronitrile and the surfactant sodium dodecyl sulfate were added, stirred evenly, and reacted at 70°C for 2.5h. After the reaction was completed, the light intensity was 3mW / cm 2 The catalyst mass is 0.3% of the mass of TiO2, and the surfactant mass is 0.8% of the mass of TiO2.

[0060] Post-treatment: After the reaction is completed, the product is centrifuged and washed with ethanol three times. The washed product is dried in an oven to constant weight to obtain modified TiO2.

[0061] Comparative Example 2

[0062] A modified TiO2, compared with Example 3, only Ce is used to modify TiO2, and Ce-modified TiO2 is not coated, and the rest is the same as Example 3, and is prepared by the following operations:

[0063] Preparation of Ce-modified TiO2: Place 3.35 L of anhydrous ethanol in a container, add 1.0 mol / L of cerium nitrate aqueous solution and mix evenly to obtain a mixed solution; add 2.65 L of titanium tetrachloride to the mixed solution while stirring until a sol-state substance is formed, react it at 150 °C for 8 h, and naturally cool it after the reaction to obtain a solid. Wash the solid three times with anhydrous ethanol, filter and dry to obtain Ce-modified TiO2, wherein the molar ratio of cerium nitrate to titanium tetrachloride is 3%.

[0064] Comparative Example 3

[0065] A modified TiO2, compared with Example 3, methyl methacrylate is used instead of N-(3-dimethylaminopropyl) methacrylamide to coat Ce-modified TiO2, and the rest is the same as Example 3, and is prepared by the following operations:

[0066] Preparation of Ce-modified TiO2: Place 3.35 L of anhydrous ethanol in a container, add 1.0 mol / L of cerium nitrate aqueous solution and mix evenly to obtain a mixed solution; add 2.65 L of titanium tetrachloride to the mixed solution while stirring until a sol-state substance is formed, react it at 150 °C for 8 h, and naturally cool it after the reaction to obtain a solid. Wash the solid three times with anhydrous ethanol, filter and dry to obtain Ce-modified TiO2, wherein the molar ratio of cerium nitrate to titanium tetrachloride is 3%.

[0067] Coating reaction: Ce-modified TiO2, sodium dodecyl sulfate and deionized water are added to the reactor in a mass ratio of 10:0.1:100, heated to 80°C, and then sodium bisulfite and ammonium persulfate are added in sequence, and the mass ratio of Ce-modified TiO2 is Ce-modified TiO2: sodium bisulfite: ammonium persulfate = 10:0.456:0.1. After stirring for 15 minutes, methyl methacrylate is added dropwise within 1 hour. After the reaction is completed, demulsify with saturated sodium chloride solution, filter under reduced pressure, wash with distilled water 3 times, dry at 45°C to constant weight, and crush to obtain modified TiO2.

[0068] The modified TiO2 of Examples 6-10 and Comparative Examples 4-6 of Examples 1-5 and Comparative Examples 1-3 were prepared according to the following method to prepare photocatalytic water-based coatings: quantitatively weigh water, cellulose, dispersant, and wetting agent and stir evenly, then add modified TiO2 and pigment for dispersion and grinding, add BASF pure acrylic emulsion (purchased from Guangzhou Xianrenhui International Trade Co., Ltd., product model: Acronal PA237) for dispersion, and then add defoamer and thickener after uniform dispersion, mix evenly, and prepare photocatalytic water-based coatings. The components and weight parts are shown in Table 1:

[0069] Table 1

[0070]

[0071] The following tests were performed on Examples 1 to 5 and Comparative Examples 1 to 3:

[0072] Test Example 1 Stability Test

[0073] 30 mL of distilled water was measured in a 100 mL beaker, and then 0.1 g of the modified TiO2 powder prepared in Examples 1 to 5 and Comparative Examples 1 to 3 was weighed and added to the solution. Ultrasonic power was 540 W for 5 min, and then magnetic stirring was performed for 0.5 h. 25 mL of the dispersion was introduced into a stoppered graduated test tube, and the tube was placed on a laboratory bench to stand. The dispersion effect of the stationary solution was observed after standing for 24 h, and the upper layer of the solution was poured into a measuring cylinder to read the volume V.

[0074] Gravity sedimentation stability = (25-V) / 25. The larger the V value, the less the sedimented powder, which means the more stable the dispersion. The results are shown in Table 2:

[0075] Table 2

[0076] Components Gravity sedimentation stability V / mL Example 1 24.4 Example 2 24.3 Example 3 24.7 Example 4 24.4 Example 5 24.1 Comparative Example 1 23.8 Comparative Example 2 23.1 Comparative Example 3 23.4

[0077] It can be seen from Table 2 that the modified TiO2 prepared in Examples 1 to 5 all showed excellent gravity sedimentation stability in the stability test, all greater than 24. The gravity sedimentation stability of the modified TiO2 prepared in Comparative Examples 1 to 3 was reduced to varying degrees compared with Example 3. The modified TiO2 in Comparative Example 1 did not use Ce to modify TiO2, and its formaldehyde purification rate did not decrease significantly. The modified TiO2 in Comparative Example 2 only used Ce to modify TiO2, and did not coat the Ce-modified TiO2, and its gravity sedimentation stability was significantly reduced. It can be seen that the coating of TiO2 effectively improved the gravity sedimentation stability of the modified TiO2. The modified TiO2 in Comparative Example 3 is coated with methyl methacrylate instead of N-(3-dimethylaminopropyl)methacrylamide for Ce-modified TiO2, and its gravity sedimentation stability is slightly improved compared with Comparative Example 2 but still decreased compared with Example 3. It can be seen that coating Ce-modified TiO2 with N-(3-dimethylaminopropyl)methacrylamide can also improve the gravity sedimentation stability of the modified TiO2.

[0078] The following tests were performed on Examples 6 to 10 and Comparative Examples 4 to 6:

[0079] Test Example 2 Formaldehyde degradation performance test

[0080] The formaldehyde degradation experiment of the coating template was tested in accordance with the JC / T1074-2021 "Purification Performance of Indoor Air Purification Function Coating Materials" standard, and a 24-hour formaldehyde purification performance test was carried out in a homemade experimental device. The experimental device consists of a closed glass box (with a test hole in the glass box), a UV lamp, and a fan, and a fan is placed to even out the air. The light intensity is 40mW·cm -2 , coating thickness is 250μm, time is 24h, test formaldehyde purification rate, the results are shown in Table 3:

[0081] Table 3

[0082] Components Formaldehyde purification rate / % Example 6 96.3 Example 7 97.8 Example 8 98.7 Example 9 98.4 Example 10 97.9 Comparative Example 4 90.7 Comparative Example 5 82.6 Comparative Example 6 91.4

[0083] As can be seen from Table 3, the photocatalyst water-based coatings prepared in Examples 6 to 10 all showed excellent formaldehyde purification rates in the 24h formaldehyde purification rate test, all greater than 96%. The formaldehyde purification rates of the photocatalyst water-based coatings prepared in Comparative Examples 4 to 6 were reduced to varying degrees compared with Example 8. The modified TiO2 in Comparative Example 4 did not use Ce to modify TiO2, and its formaldehyde purification rate was significantly reduced. It can be seen that Ce modification effectively improved the formaldehyde purification rate of the water-based coating. The modified TiO2 in Comparative Example 5 only used Ce to modify TiO2, and did not coat the Ce-modified TiO2. Its formaldehyde purification rate was also significantly reduced. It can be seen that coating TiO2 effectively improved the formaldehyde purification rate of the water-based coating. In the modified TiO2 in Comparative Example 6, methyl methacrylate is used instead of N-(3-dimethylaminopropyl)methacrylamide to coat the Ce-modified TiO2, and its formaldehyde purification rate is slightly improved compared with Comparative Example 5 but still significantly decreased compared with Example 8. It can be seen that coating Ce-modified TiO2 with N-(3-dimethylaminopropyl)methacrylamide can also improve the formaldehyde purification rate of photocatalyst water-based coatings.

[0084] The above is only an implementation method of the invention, and does not limit the scope of patent protection. Those skilled in the art can make non-substantial changes or substitutions based on the invention, which still fall within the scope of patent protection.

Claims

1. A photocatalyst water-based paint, characterized in that: The invention relates to a photocatalyst material-modified TiO2, wherein the modified TiO2 is prepared by the following operations: Preparation of Ce-modified TiO2: evenly mix anhydrous ethanol and cerium nitrate aqueous solution to obtain a mixed solution; mix the mixed solution with titanium tetrachloride, heat to react, and cool after the reaction to obtain Ce-modified TiO2; Pretreatment: crush Ce-modified TiO2 into powder and then disperse it in ethanol by ultrasonic to obtain a 5-10wt% TiO2 suspension; dissolve N-(3-dimethylaminopropyl)methacrylamide in ethanol to obtain a 8-12wt% mixed solution; Coating reaction: Mix the TiO2 suspension prepared in the pretreatment with the mixed solution, then add the catalyst ammonium persulfate or azobisisobutyronitrile and the surfactant sodium dodecyl sulfate, mix well, heat to react, and irradiate with ultraviolet light after the reaction is completed; Post-treatment: After the ultraviolet lamp irradiation is completed, the product is centrifuged and dried to obtain modified TiO2.

2. The photocatalyst water-based paint according to claim 1, characterized in that: In the preparation of Ce-modified TiO2, the concentration of the cerium nitrate aqueous solution is 0.5-1.5 mol / L.

3. The photocatalyst water-based paint according to claim 1, characterized in that: In the preparation of Ce-modified TiO2, the temperature of the heating reaction is 130-180°C, and the time of the heating reaction is 6-10 hours.

4. The photocatalyst water-based paint according to claim 1, characterized in that: In the preparation of Ce-modified TiO2, the molar ratio of cerium nitrate to titanium tetrachloride is 1-5%.

5. The photocatalyst water-based paint according to claim 1, characterized in that: During the coating reaction, the mass ratio of TiO2 to N-(3-dimethylaminopropyl)methacrylamide is controlled to be 1:50-60.

6. The photocatalyst water-based paint according to claim 1, characterized in that: In the coating reaction, the temperature rise reaction is specifically a reaction at 60-80° C. for 1.5-3.5 hours.

7. The photocatalyst water-based paint according to claim 1, characterized in that: In the coating reaction, the ultraviolet light irradiation is specifically used with a light intensity of 2-4 mW / cm 2 Irradiate with ultraviolet light for 20 to 30 minutes.

8. The photocatalyst water-based paint according to claim 1, characterized in that: In the coating reaction, the mass of the catalyst is 0.1-1% of the mass of TiO2, and the mass of the surfactant is 0.5-1% of the mass of TiO2.

9. The photocatalyst water-based paint according to claim 1, characterized in that: Contains the following components in parts by weight: 30~50 parts water Cellulose 0.1~0.5 parts Dispersant 1~2 parts Wetting agent 0.1~2 parts Modified TiO2 3~12 parts Pigment 10~20 parts BASF pure acrylic emulsion 20~30 parts Defoaming agent 0.1~0.4 parts 1~3 parts of thickener.

10. The method for preparing the photocatalyst water-based coating according to claim 9, characterized in that: The method comprises the following steps: quantitatively weighing water, cellulose, dispersant and wetting agent, stirring evenly, adding modified TiO2 and pigment for dispersion and grinding, adding BASF pure acrylic emulsion, adding defoamer and thickener after dispersion evenly, mixing evenly, and preparing photocatalyst water-based coating.

Citation Information

Patent Citations

  • Composite metal ion doped with TiO2 photocatalyst transparent emulsion and preparation method thereof

    CN101380568A

  • Rare earth doped nanometer TiO2 photocatalyst emulsion

    CN103861578A

  • Polymer-coated perovskite quantum dots and preparation method thereof

    CN109306265A

  • Preparation method of nitrogen-doped TiO2 microspheres with hollow core-shell structure

    CN110605134A

  • Metal-doped titanium oxide toner as well as preparation method and application thereof

    CN113620341A